HEALTH-RELATED QUALITY OF LIFE AFTER KIDNEY TRANSPLANTATION: CURRENT EVIDENCE AND CLINICAL IMPLICATIONS (Global Conference on Medical and Health Sciences, 2026)
Background:Kidney transplantation is the preferred treatment for end-stage renal disease, offering survival benefits over dialysis. However, long-term outcomes increasingly focus on health-related quality of life (HRQoL). Objective: To analyze contemporary evidence on HRQoL after kidney transplantation and identify key determinants affecting patient outcomes. Methods: Narrative review of recent studies (2020–2026) addressing HRQoL, psychological status, and clinical determinants in kidney transplant recipients. Results: Kidney transplantation significantly improves HRQoL compared to dialysis, particularly in physical and social domains. However, HRQoL remains lower than in the general population. Immunosuppressive therapy, psychological disorders, and comorbidities are major limiting factors. Conclusion: HRQoL should be considered a core outcome in transplant medicine, requiring multidisciplinary management and individualized therapeutic strategies.
Keywords: Kidney transplantation, quality of life, HRQoL, immunosuppression, renal failure